2014
DOI: 10.1111/acem.12344
|View full text |Cite
|
Sign up to set email alerts
|

Occult Pneumothoraces in Children With Blunt Torso Trauma

Abstract: Objectives: Plain chest x-ray (CXR) is often the initial screening test to identify pneumothoraces in trauma patients. Computed tomography (CT) scans can identify pneumothoraces not seen on CXR ("occult pneumothoraces"), but the clinical importance of these radiographically occult pneumothoraces in children is not well understood. The objectives of this study were to determine the proportion of occult pneumothoraces in injured children and the rate of treatment with tube thoracostomy among these children.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…1,2 In adults, pneumothoraces can occur in up to 64% of the most severely injured, ventilated patients. 3 Currently there is no clinical consensus on how to treat occult versus overt pneumothoraces in adults, and even less research has been done in children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,2 In adults, pneumothoraces can occur in up to 64% of the most severely injured, ventilated patients. 3 Currently there is no clinical consensus on how to treat occult versus overt pneumothoraces in adults, and even less research has been done in children.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study with a larger population of ventilated children showed a progression rate up to 38%. 2 Our objective was to understand how our institution has managed occult pneumothoraces in severely injured children on mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One large study of more than 8000 pediatric trauma patients reported that tube thoracostomy was performed in 57.4% of patients with nonoccult pneumothorax (PTX) and 15.6% of patients with OPTXs, with an interfacility range of 0% to 49% for all PTXs. 2 However, studies on the need for intervention in patients with OPTXs are difficult to interpret, as tube thoracostomy might be performed prophylactically, without clear patient decompensation. When end points of patient decompensation or PTX expansion are studied, smaller studies demonstrate these outcomes in approximately 6% of all patients, 3 with even lower frequency for children.…”
mentioning
confidence: 99%